Voices & Visions : (Random House, 1987)
A college text and companion volume to a new PBS television series, this collection of essays on 13 American poets from Whitman to Plath is traditional in selection and treatment. Punctuated with poems and illustrated with photographs and manuscript facsimiles showing authors' revisions, the book seeks to explore the poets' "American-ness"but often runs short of the historical, social, and biographical background needed for the task. Occasionally an essay presents a labored academic "explanation" giving an entirely different and unnecessary reading from the common-sense reading most readers find enjoyable. But the many useful essays on Pound, Bishop, Plath, Hughes, Dickinson, and others make this a solid introductory guide. ( Library Journal)